Annual Report, 2015 - Kansas State University; University of Illinois; Oklahoma State University; University of Kentucky; University of Nebraska – Lincoln; South Carolina State University; Ft. Valley State University; USDA-ARS Center for Grain and Animal Health Research (My University, 2017)
The Feed the Future Reduction of Post-Harvest Loss Innovation Lab is a strategic and applied, research and education program aimed at improving food security by reducing post-harvest loss and food waste of seeds and durable staple crops, e.g., grains, oilseeds, and legumes. The Lab’s efforts are focused in four Feed the Future countries (Bangladesh, Ethiopia, Ghana, and Guate-mala) and Afghanistan.
Feed the Future: Reduction of Post-Harvest Loss Innovation Lab. October 2014 - September 2015
Keywords: USAID; Innovation Lab; Post-Harvest Loss; Food Waste; Durable Staple Crops; Crop Seeds